Tooth Wear and Tribological Investigations in Dentistry - Ran Wang; Yuanjing Zhu; Chengxin Chen; Yu Han; Hongbo Zhou (Applied Bionics and Biomechanics)
Dental or tooth wear is a physiological process in the life cycle of teeth. Loss of the occlusal surface may cause excessive tooth wear. Several factors may contribute to tooth wear with different intensities and duration in the oral cavity. The oral cavity is generally compared to a tribological system to determine the various types of wear between teeth and restorative materials and assess the amount of dental wear. However, it is challenging to investigate in vitro and in vivo wear owing to the complexity of tooth wear; thus, a clear correlation between in vitro and in vivo data could not be established. This review is aimed at providing an insight into the etiology of tooth wear and tribological investigations in dentistry.